2020
DOI: 10.1088/1755-1315/486/1/012121
|View full text |Cite
|
Sign up to set email alerts
|

Growth and production of Katokkon (Capsicum chinense Jacq) chili plants in lowland applied with gibberellins and liquid organic fertilizer

Abstract: This study aimed to determine the growth and production of katokkon chili plants (Capsicum chinense Jacq.) in the application of gibberellins and liquid organic fertilizer. This research was conducted at the Experimental Farm of the Faculty of Agriculture, Universitas Hasanuddin, Makassar from May to October 2017. The research was conducted in the form of a two-factors factorial experiment. The first factor was gibberellins consisted of four levels namely 0 ppm, 25 ppm, 50 ppm and 75 ppm, and the second factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…1). Cignore katokkon it only grows well in the highlands with altitudes ranging from 1000-1500 meters above sea level and is susceptible to temperatures around 16-24 °C [13]. Rain intensity required for optimal growth is around 1500-3500 mm/year with humidity around 82-86%.…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…1). Cignore katokkon it only grows well in the highlands with altitudes ranging from 1000-1500 meters above sea level and is susceptible to temperatures around 16-24 °C [13]. Rain intensity required for optimal growth is around 1500-3500 mm/year with humidity around 82-86%.…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…Information related to seeds of various chili such as Habanero chili and Katokkon chili (Capsicum chinense Jacq.) [22,23], Ancho and Guajillo chili (Capsicum annuum L.) [24][25][26], Capsicum frutescens L. [27,28], Capsicum baccatum [29] have been reported. Likewise, reports related to seed productions of local chili varieties (Odeng, Lanyoe, Super Amando, and Lamando Lapaben from Aceh [30]; Katokkon chili from Sulawesi [23]; Pulau Timor [31]) or nasional varieties (IPB CH1, IPB CH2, IPB CH3, IPB CH4, IPB CH5, IPB CH6, IPB CH25, IPB CH28, and IPB CH50 varieties owned by IPB University [32]; UNIB C H73, UNIB C H65, and UNIB C H13 varieties owned by Universitas Bengkulu [33]; CK5 variety owned by Universitas Padjadjaran [31]; PM999, Kiyo [34], or Arimbi [35] varieties owned by private companies have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[22,23], Ancho and Guajillo chili (Capsicum annuum L.) [24][25][26], Capsicum frutescens L. [27,28], Capsicum baccatum [29] have been reported. Likewise, reports related to seed productions of local chili varieties (Odeng, Lanyoe, Super Amando, and Lamando Lapaben from Aceh [30]; Katokkon chili from Sulawesi [23]; Pulau Timor [31]) or nasional varieties (IPB CH1, IPB CH2, IPB CH3, IPB CH4, IPB CH5, IPB CH6, IPB CH25, IPB CH28, and IPB CH50 varieties owned by IPB University [32]; UNIB C H73, UNIB C H65, and UNIB C H13 varieties owned by Universitas Bengkulu [33]; CK5 variety owned by Universitas Padjadjaran [31]; PM999, Kiyo [34], or Arimbi [35] varieties owned by private companies have also been reported. Information related to the potential and quality of seeds owned by the Ministry of Agriculture already exists but there are still few who report as a whole related to the potential productions and seed qualities [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…PGR can improve the process of photosynthesis, root growth, and fruit production in tomato. Research has shown that the use of a combination of LOF and PGR in plant cultivation can improve the quality and quantity of soluble sugars, vegetative and generative growth (Suherman et al, 2017;Gao et al, 2020;Kasim et al, 2020). The PGR is directly involved in regulating senescence, flowering, seed germination, regulating physiological processes, and increasing fruit formation (Zahid et al, 2023).…”
Section: Introductionmentioning
confidence: 99%